Effect of pre-curing process on epoxy resin foaming using carbon dioxide as blowing agent. (March 2017) - Lyu, Jiaxun; Liu, Tao; Xi, Zhenhao; Zhao, Ling
A thermosetting epoxy resin system consisting of diglycidylether of bisphenol A (DGEBA) and m-xylylenediamine (MXDA) was successfully foamed by carbon dioxide (CO2 ) using two-step batch process. Isothermal curing kinetics of epoxy system was developed to help control the pre-curing degree of resin under different pre-curing conditions. Samples with different pre-curing degrees were prepared and then foamed via temperature-rising foaming process. It was found that the pre-curing degree was a crucial index for the foamability of epoxy resin. The effects of pre-curing conditions on curing reaction as well as further foaming results were investigated, and the results showed that the pre-curing degree from 37.7% to 46.3% was the proper foaming range for the chosen epoxy resin. With increasing pre-curing degrees from 37.7% to 51.6%, viscosity and elasticity of pre-cured resins increased, and correspondingly, average cell size of epoxy foams decreased from 329.8 µm to 60.8 µm while cell density increased from 1.4 × 10 5 cells/cm 3 to 8.6 × 10 5 cells/cm 3 . Furthermore, the foamed samples with the same pre-curing degree had similar cell morphology regardless of pre-curing conditions.